The Impact Of E-Lapkin Implementation on The Discipline and Performance Effectiveness of School Supervisors In Lebak Regency - Usep Saepul Anwar; Syadeli Hanafie; Luluk Asmawati (LPPM Universitas PGRI Sumatera Barat, 2023)
The geographical challenges in Lebak Regency often hinder the supervision process, resulting in suboptimal reporting systems and low work discipline among school supervisors. This study aims to analyze the impact of the Electronic Performance Report Application (E-LAPKIN) implementation on the work discipline and performance effectiveness of school supervisors within the Lebak Regency Education Office. Employing a quantitative approach, this research evaluates the transformation from manual reporting to a digital-based system. Data were collected through surveys and performance records involving school supervisors. The results demonstrate that the implementation of E-LAPKIN has a significant positive impact on work discipline, driven by real-time attendance and geo-tagging features. Furthermore, the application enhances performance effectiveness by streamlining bureaucratic procedures and increasing data accuracy. This study concludes that digital transformation through E-LAPKIN is an effective policy solution to overcome geographical barriers and improve public service accountability in the education sector